Essays on public debt, growth and development in Africa - Veiga, José Augusto Lopes da (2018)
This thesis is entitled “Essays on Public Debt, Growth and Development in Africa” and consists of a set of four essays, three of which are empirical. The first essay provides a literature survey on public debt and economic growth, specially focused on Africa. Since the beginning of the 1990s, public debt has been a real barrier to the economic growth of African economies and has since become part of the agenda and concern of policy makers, economists and researchers. A considerable number of theoretical and empirical studies have been produced over decades, addressing the impact of public debt on the economic growth of these countries. The results are consensual and point generally to an inverse relationship between the two variables i.e. public debt negatively affects economic growth from a given level. Krugman (1988) and Sachs (1989) agree that high levels of public debt mitigate the economic growth of developing countries through investment. This position is further corroborated by Mbale (2013) who referring to African countries argues that public debt crowds out credit to the private sector and constitutes a barrier to capital accumulation and private sector growth. Buchanan (1958) and Modigliani (1961) also share the view that in addition to the crowding out effect, the increase in public debt positively affects the long-term interest rate. Generally, the increase in public debt negatively affects economic growth. Fosu (1996) Irons and Bivens (2010) are decisive in concluding that high debt levels jeopardize economic growth, a position shared by Ezeabasili et al (2011), Escobar and Mallick (2013) and Zouhaier and Fatma (2014). Regarding the impact of fiscal policy on the economic growth of African countries, Devarajan et al. (1996) consider, after empirical analysis, that an increase in public spending has a positive and significant impact on economic growth. Nurudeen and Usman (2010) argue that an increase in public spending is not immediately converted into economic growth, whereas Nworji et al. (2012) show that current and capital expenditures do not have a significant negative impact on Nigeria's economic growth. This view is supported by Engen and Skinner (1997) who concluded that public expenditure and the tax burden negatively and sharply affect economic growth. Babadola and Aminu (2011) provide complementary evidence and recommend that increased public spending on health and education should promote growth. The survey also highlights the inverse relationship between economic growth and government debt, compounded by the problem of debt overhang, preventing these countries from leveraging their economies. Additionally, the literature on the relationship between public deficits and economic growth is also not consensual. In fact, although the economic theory postulates that fiscal deficit contributes inevitably to debt accumulation, which through debt overhang affects negatively economic growth, there are other strings of economic thoughts that advocate that African countries would not reach economic growth without increasing debt. The second essay is empirical and analyzes the implications of public debt on economic growth and inflation in a group of 52 African economies between 1950 and 2012. The overall analysis was focused on the relationship between the limits of public debt as a percentage of the GDP, economic growth, and inflation. African economies achieve their highest performance in terms of average rates of economic growth (6.39%), while the limits of public debt as a percentage of the GDP are in the second intervals (30 - 60%) with an average inflation rate of 8.17%. From this limit, any increase in public debt is converted into a reduction of the average growth rates of economies and into an increase in average inflation rates. The findings show, unequivocally, that there is an inverse relationship between these two macroeconomic variables, depending on the levels of indebtedness. Briefly, the analysis concludes that the highest average growth rates are achieved when the public debt is in the second interval. When this ratio is situated in the third interval the average rates of economic growth suffer a drop of 1.32 percentage points and 1.64 percentage points when this ratio exceeds 90%. These results are much lower than those found by Reinhart and Rogoff in the essay “Growth in Time of Debt”, for which an amount of debt equivalent to 60% of GDP causes a drop in the annual growth rate of around 2 percentage points. The third essay empirically assesses the traditional determinants of economic growth in African economies over the period 1950 to 2012, using growth regression techniques in which the explanatory variables are: public debt per capita, investment ratio, government ratio, capital stock per capita, and the Human Capital Index. The method used takes into account observed and unobserved heterogeneity. The regression results show strong evidence of a positive impact of the growth rate of capital stock to economic growth of African countries. The growth rate of the government to GDP ratio is also important in all but one of the regressions in which appears, and its growth is harmful for economic growth. Human capital has a positive relationship with economic growth in regressions that don’t include public debt. However, the cross country impact of these two variables on the growth rate of the economies (positive to some and negative to others) is not uniform, so that appropriate policies for one country may be seriously misguided in another. Concerning public debt, we found that it is not significant and therefore it has no impact on the economic growth of African countries. The growth rate of real GDP per capita also depends (negatively) on its past value, i.e., the lower the real GDP per capita the higher will be its growth rate. We have also tested two proxies for institutions, which did not deliver significant results. The software used for the regressions is STATA, version 13. The fourth essay is devoted to an exploratory analysis of the main economic, social and institutional determinants of development in Africa, using a main component analysis for categorical data and cluster analysis and taking into account the years 1996 and 2014 as the oldest and most recent, respectively. This methodology allowed the agglomeration of the African countries into four differentiated clusters, being the countries constituting the clusters of 1996 distinct from those of the year 2014. The results point out to a positive association between the social, economic and institutional determinants of development which is reflected in the fact that countries with better institutional performances also show better indicators of economic and social achievement. The results also draw the attention of policy makers and development strategists to the need for an integrated approach to the development process, in order to achieve greater and more efficient integration of the different development determinants. The software used is IBM-SPSS (Statistical Package for Social Sciences), version 23.0.